2018
DOI: 10.1080/13552600.2018.1476601
|View full text |Cite
|
Sign up to set email alerts
|

Female sex offenders who abuse children whilst working in organisational contexts: offending, conviction and sentencing

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
20
2
Order By: Relevance
“…Contrary to public perceptions, Darling et al (2018) found through their in-depth case analysis of professional regulator decisions, media reports, court reports, and relevant website content, these female perpetrators were neither inexperienced naïve teachers nor fit the stereotype of females coerced by men to offend against young children. Most appeared to offend as a result of situational and contextual factors rather than any evident sexual preference for children or pre-disposition to sexually offend.…”
Section: Literature Reviewcontrasting
confidence: 58%
See 4 more Smart Citations
“…Contrary to public perceptions, Darling et al (2018) found through their in-depth case analysis of professional regulator decisions, media reports, court reports, and relevant website content, these female perpetrators were neither inexperienced naïve teachers nor fit the stereotype of females coerced by men to offend against young children. Most appeared to offend as a result of situational and contextual factors rather than any evident sexual preference for children or pre-disposition to sexually offend.…”
Section: Literature Reviewcontrasting
confidence: 58%
“…These women shared similarities found in other female sexual offender studies, including unstable lifestyles, relationship difficulties, emotional self-management problems, low self-esteem, isolation, and loneliness. However, there was less evidence of substance abuse, mental health problems, chaotic backgrounds, and previous victimisation among these women (Darling et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 87%
See 3 more Smart Citations